POTENCY OF SOLID WASTE OF PAPER MILL USING RECYCLE PAPER AS FUEL - Yusup Setiawan; Sri Purwati; Krisna Aditya Wardhana; Aep Surahman; Reza Bastari Wattimena (Center for Pulp and Paper, 2012)
The paper industry generates solid waste such as wastewater sludge and paper mill rejects. The rejects from recycled paper processing are varies from 5 % to 25 % dependent on the recovered fiber quality and process used in the mill. The composition of the rejects is consisted of fiber bundles, plastics pieces, foils and polystyrene containing large quantities of plastics. One of the limitations of solid waste for energy is bulky and high moisture content which is difficult to be stored, transported, and utilized. To overcome this limitation, it is needed a solidification process. Pelletizing of paper mill solid waste is one of solidification processes to ease in storing, handling, and transporting of solid waste. Experiment on solid wastes utilization in the pellet form as fuel has been carried out. Solidification process of paper mill solid waste is consisted of drying, shredding and pelletizing processes of solid waste. Pellet of paper mill solid waste and coal and pellet of combination of rejects waste were analyzed for their proximate, mineral content of ash and ash fusion temperature (AFT) to see slagging and fouling potency. The results shows that paper mill reject contain high calorific value of 5,987 calorie/gram and low content of sulphur and ash. Ash has low content of total alkali (Na2O and K2O) and high initial deformation temperature (IDT) of 1,193oC. Mixed of 95% coal and 5% pellet of reject waste has low content of total alkali (Na2O and K2O) and high initial deformation temperature (IDT) of 1,315oC. The result indicates low slagging and fouling potency of reject waste when it is utilized as a boiler fuel.Keywords: solid waste, sludge, rejects, pellet, fuel, slagging, fouling ABSTRAK Industri kertas menghasilkan limbah padat seperti limbah lumpur dan limbah reject. Jumlah limbah reject dari pengolahan kertas daur ulang bervariasi dari 5% sampai 25% tergantung pada kualitas serat dan proses yang digunakan di pabrik. Komposisi limbah reject terdiri dari gumpalan serat, potongan plastik dan foil. Salah satu keterbatasan dari limbah padat untuk energi adalah ruah dan kadar air-nya tinggi yang menyulitkan dalam penyimpanan, transportasi, dan penggunaannya. Untuk mengatasi keterbatasan ini diperlukan proses solidifikasi. Pembuatan pellet dari limbah padat industri kertas merupakan salah satu proses solidifikasi untuk memudahkan dalam penyimpanan, penanganan, dan pengangkutan limbah padat. Penelitian pemanfaatan limbah padat dalam bentuk pelet sebagai bahan bakar untuk energi telah dilakukan. Proses solidifikasi limbah padat pabrik kertas terdiri dari proses pengeringan, proses pencacahan dan proses pembuatan pellet. Pellet limbah padat industri kertas dan campuran dari batubara dan pellet limbah reject diuji untuk analisis proksimat, kadar mineral abu, kadar abu dan suhu fusi abu (AFT) untuk mengetahui potensi slagging dan fouling. Hasil menunjukkan bahwa limbah reject industri kertas mengandung nilai kalor tinggi 5.987 kalori/gram dan rendah sulfur dan abu. Abu mengandung alkali total (Na2O dan K2O) rendah dan suhu deformasi awal tinggi (IDT) yaitu 1.193oC. Campuran dari batubara 95% dan pellet limbah reject 5% mengandung alkali total (Na2O dan K2O) rendah dan suhu deformasi awal tinggi (IDT) yaitu 1.315oC. Hal ini menunjukkan potensi slagging dan fouling rendah bilamana limbah reject digunakan sebagai bahan bakar boiler.Kata kunci: limbah padat, lumpur, reject, pelet, bahan bakar, slagging, fouling